Participation, Identity and socio-emotional skills in a community of practice: The case of an agricultural and tambera cooperative - Martín, Rocío Belén; Silvio Donolo, Danilo; Magallanes, Graciela Susana (Cooperativismo & Desarrollo, 2021)
The purpose of the document presented here is, on the one hand, to explore the socio-emotional skills of the members of a cooperative in relation to the work they do, analyzing their influence on the construction of personal and collective identity; and on the other hand, attend to the learning, education and participation processes in the formation and consolidation of a community of practice. The case of an agricultural and tambera cooperative was studied: “El Craikense”, dedicated to dairy production since 1926, and located in the province of Córdoba, Argentina. For this study, an in-depth interview was conducted with the president of the cooperative, the observations recorded from the ordinary general assembly and the memory and balance documents were analyzed. Among the results found, the cooperative could be understood as a community of practice crossed by processes of joint participation, co-construction of identities and socio-emotional skills with an emphasis on the interpersonal. The cooperative as a community fostered collective learning among members through the exchange of experiences; sharing and creating knowledge and knowledge to improve the impact of the cooperative project in the region.